The Interconnectedness of Others, Self, and God: Unmarried Older Balinese Women’s Journeys Toward a Meaningful Life - Made Selphia Prahasasgita; Made Diah Lestari (Pusat Kajian Bali Universitas Udayana, 2025)
Our society constructs women’s roles as wives and mothers. Likewise, the Balinese positions women as caretakers who are obligated to marry, provide offspring, and look after their family. Therefore, women who choose to be single, especially until late adulthood, are stigmatised as selfish and immature. This study aims to understand what constitutes a meaningful life for unmarried older women and the related factors that support a meaningful life. The participants were five unmarried older Balinese women. Interview data were analysed using reflexive thematic analysis by Braun & Clarke and show that a meaningful life for unmarried older women consists of Others (meaningful social relationships), Self (being grateful in life), and God (believing in God). To achieve a meaningful life, self-acceptance as an older and unmarried person is needed. The findings are expected to inform policies and programs that emphasise the social activity and connection between older people and their communities.